Perceived Service Quality and Customer Satisfaction in Nepalese Banking Industry - Joshi, Chhemanand (Contemporary Research: An Interdisciplinary Academic Journal, 2021)
The main purpose of this study was to examine the relationship between banking service quality dimensions and customer satisfaction in Nepalese banking industry. Three commercial banks operating in Kailali district (Rastriya Banijya Bank, Nabil Bank and Global IME bank) were taken as sample and 327 depositor customers of these banks were surveyed using structured five point Likert scale questionnaire. Data was collected via online and field survey by visiting the customers at related banks, business organizations and government and non government offices of Kailali. SPSS version 20, Pearson’s correlation and multiple regression analysis have been used to analyze the data. The findings of this study revealed that there is positive relationship between service quality and customer satisfaction. All the service quality dimensions have statistically significant positive impact on customer satisfaction except tangibility. It means higher service quality helps increase customer satisfaction. The results of this study will help bank mangers to focus on their customer’s satisfaction in order to compete favorably in banking Industry. Future researchers can conduct their study focusing on mediating effect of customer satisfaction in service quality and customer loyalty. Effect of demographic variables on satisfaction is also unanswered in this study so, further study can be done including moderating effect of demographic variables.